Fetal magnetic resonance imaging in the confirmation of congenital anomalies found on routine mid-trimester ultrasound - Dhaifalah, Ishraq; Godava, Marek; Havalova, Jana; Hanzlikova, Pavla; Michalkova, Kamila; Bakaj Zbrozkova, Lenka; Civrny, Jakub; Cuckle, Howard (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2024)
OBJECTIVE: To determine the added value of fetal magnetic resonance imaging (MRI) when clarifying a suspected anomaly detected by mid-trimester scan. METHODS: Women attending two centers of fetal medicine between January 2017 and December 2021 were identified. The centers carried out routine mid-trimester ultrasound scans to detect fetal anomalies. Those with a suspected anomaly which required further clarification were referred for fetal magnetic resonance imaging (MRI). The medical records of all referred women were examined to determine the anomalies found at scan, MRI and termination of pregnancy or delivery. A total of 9571 women had a routine mid-trimester scan and an anomaly was either diagnosed or suspected in 449 (4.7%); an MRI examination was made in 76 cases (0.79%). RESULTS: MRI confirmed the presence of an abnormality in 61 referrals (80%) and failed to yield a result in one case. Outcome information was available for 69 cases: the MRI confirmation rate was 89% (48/54) in those with abnormal outcome and 40% (6/15) if the outcome was normal, P.
Keywords: druhý trimestr těhotenství; těhotenství; developmental; prenatal diagnosis; Adult; magnetic resonance imaging; anomaly scan; magnetická rezonanční tomografie; Magnetic Resonance Imaging; ženské pohlaví; mid-trimester; Humans; Pregnancy; Congenital Abnormalities; Ultrasonography, Prenatal; Prenatal Diagnosis; dospělí; prenatální diagnóza; Female; ultrasonografie prenatální; Pregnancy Trimester, Second; vrozené vady; lidé